Subject positioning in marketing discourse - Selezneva, L. V. (Diskurs pi : filosofii͡a︡, politika, vlastʹ, svi͡a︡zi s obshchestvennostʹi͡u︡ : Di pi = Discourse P : philosophy, politics, power, public relations, 2024)
Positioning is a special form of communication process that includes marketing and advertising activities to provide a company or product with a certain place (i.e. position) on the market. At the same time, companies actively use different marketing communication strategies in social media. The concept of positioning was developed in the 90s of the 20thcentury and it still remains one of the most popular marketing theories, however there is certainly ambiguity in understanding how the process of positioning is performed and what are the mechanisms of its analysis in terms of discursology. On the one hand, positioning is considered as a result of interaction between levels, i.e. between a creator, a referent and a recipient and their mutual inﬂuence, and on the other as positions applied by subjects. Therefore, the goal of this paper is to determine a discursive mechanism of positioning. The research was based on methodological principles of discoursology, which made it possible to identify positions of participants in communicative interaction and thereby describe the main forms and mechanisms of positioning in marketing discourse. The analysis shows a certain dynamics of positioning regarding a possible change in positions taken by positions, both due to their own intentions and inﬂuenced by the opinions of other subjects within interaction. Facebook, Instagram3 and Twitter4 offcial accounts of the companies were used to present such communication strategies as establishing contact and coordinating positions, which are implemented in the process of intersubject interaction. The conducted analysis of interaction between different levels, i.e. a subject, an object and other subjects, revealed that positioning seems to provide a subject of speech with the position to an object and other subjects, as well as it seems to determine a subject’s attitude to the actions of others and their opinion about an object of positioning.